Predictors of preventive behavior in healthy women attending a breast clinic - Βλαβιανού Μ.; Αναγνωστόπουλος Φ.; Καρυδά Ε.; Καλαντζή-Αζίζι Α. (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF